2014
DOI: 10.3390/educsci4010087
|View full text |Cite
|
Sign up to set email alerts
|

Digital Tools Disrupting Tertiary Students’ Notions of Disciplinary Knowledge: Cases in History and Tourism

Abstract: This paper reports on the findings from a two year research project that explored the potential of digital tools in support of teaching-learning across different disciplinary areas at a New Zealand university. Two courses (in History and Tourism) are case studied using data collected through interviews with lecturers, tutors and their students, and an online student survey. Findings from the research revealed that both lecturers and students were challenged in learning about the affordances and use of the lect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Collectively, the seven journal articles in this Special Issue provide insights into the genesis of eLearning from as far back as 1977 and trends through until 2005 [10], highlights the relationship between research, policy and practice [1,10], proposes that we need to rethink schooling in a networked world [7], and provides guidance into models for building the capabilities and capacity for designing eLearning [6,8,9,11]. As indicated in the introduction to this Editorial, we need to remember that we are in the early, formative stages of the 21st Century.…”
Section: It Is Important To Step Back From the Current Elearning Devementioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, the seven journal articles in this Special Issue provide insights into the genesis of eLearning from as far back as 1977 and trends through until 2005 [10], highlights the relationship between research, policy and practice [1,10], proposes that we need to rethink schooling in a networked world [7], and provides guidance into models for building the capabilities and capacity for designing eLearning [6,8,9,11]. As indicated in the introduction to this Editorial, we need to remember that we are in the early, formative stages of the 21st Century.…”
Section: It Is Important To Step Back From the Current Elearning Devementioning
confidence: 99%
“…Bronwen Cowie and Elaine Khoo report on the findings of a research project, conducted in a New Zealand University, which aimed to increase our understandings of the ways in which digital tools can develop, challenge and expand the learning of tertiary students. In Digital Tools Disrupting Tertiary Students' Notions of Disciplinary Knowledge: Cases in History and Tourism [8], they reported that lecturers and students were challenged in learning about the affordances of the technologies. Their prior thinking became disrupted which led to new understandings of the discipline areas studied, namely, History and Tourism, and of effective pedagogical approaches enabled by the technologies employed.…”
mentioning
confidence: 99%
“…From the above, it is understood that notable interest exists in academic research on the literacy of university students [1,19,31] characterized by a constant adaptation to the new demands derived from the changes experienced by the social environment, which are caused, to a large extent, by technological development [10,16,19,32]. Another feature that defines research on literacy, and specifically on DL, is its focus or specialization in specific areas or disciplines in response to the different levels of demand that professional sectors require of graduates [9,[33][34][35], including the tourist field [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, DL must provide students, in general, with the necessary qualification to face the challenges of the digital information age [15,43,44]. This maxim acquires greater relevance among tourism students [38,40] due to the growing impact that ICTs have had on the sector [45][46][47][48] and because the forecast, based on the pandemic we are experiencing, is that it will keep growing [49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation